If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (R + 10)(r + 2) = -15 Reorder the terms: (10 + R)(r + 2) = -15 Reorder the terms: (10 + R)(2 + r) = -15 Multiply (10 + R) * (2 + r) (10(2 + r) + R(2 + r)) = -15 ((2 * 10 + r * 10) + R(2 + r)) = -15 ((20 + 10r) + R(2 + r)) = -15 (20 + 10r + (2 * R + r * R)) = -15 (20 + 10r + (2R + rR)) = -15 Reorder the terms: (20 + 2R + 10r + rR) = -15 (20 + 2R + 10r + rR) = -15 Solving 20 + 2R + 10r + rR = -15 Solving for variable 'R'. Move all terms containing R to the left, all other terms to the right. Add '-20' to each side of the equation. 20 + 2R + 10r + -20 + rR = -15 + -20 Reorder the terms: 20 + -20 + 2R + 10r + rR = -15 + -20 Combine like terms: 20 + -20 = 0 0 + 2R + 10r + rR = -15 + -20 2R + 10r + rR = -15 + -20 Combine like terms: -15 + -20 = -35 2R + 10r + rR = -35 Add '-10r' to each side of the equation. 2R + 10r + -10r + rR = -35 + -10r Combine like terms: 10r + -10r = 0 2R + 0 + rR = -35 + -10r 2R + rR = -35 + -10r Reorder the terms: 35 + 2R + 10r + rR = -35 + -10r + 35 + 10r Reorder the terms: 35 + 2R + 10r + rR = -35 + 35 + -10r + 10r Combine like terms: -35 + 35 = 0 35 + 2R + 10r + rR = 0 + -10r + 10r 35 + 2R + 10r + rR = -10r + 10r Combine like terms: -10r + 10r = 0 35 + 2R + 10r + rR = 0 The solution to this equation could not be determined.
| AX-C=D-BX | | 15*X/8=24 | | 5+0.01x=0.025x | | 15x+10-2x=3x-7 | | 11x^2-14=30 | | 15X+9=6X+81 | | f(x)=4x^2-8x+6 | | 1/2*90 | | 4x-7/5 | | 2x+1=-3(2x+9) | | 18x^3+12x^2-16x=0 | | -15n+6=-13n-10 | | -3y-8=6y+46 | | 150x-5x=0 | | x^2-50=23x | | -7x+8-10x^2=7 | | h=1600t-16t | | 16+12x-8=20-4x | | 7.5(x-1)=-0.5x+40.5 | | .05x+.10y=2.40 | | X(x-5)(x+3)=0 | | 10x+5=13+6x | | 248-18= | | 7x+2-8x=9 | | 27-5+10x=15-3x | | 4y-y+9y=-5 | | 9w^4+30w^3+21w^2= | | ((1/(x^(1/2)))-(1/(c^(1/2))))/(x-c) | | 5k^2+43=-56 | | 7x-1+6x=4 | | 3y+2y=180-27-5+7 | | f+9-6=2 |